LINGUSTIC ANALYSIS ОF SOME MORPHOSYNTACTIC АND LEXICAL CHARASTERISTICS ОF SOCIAL COMMUNICATION IN ITALY - Shrempf, Luciana Guido (PALIMPSEST / ПАЛИМПСЕСТ, 2018)
The present study aims to identify some of the main features at the morphosyntactic and lexical level of the language used in Italian social communication through the analysis of a large number of announcements made from the seventies to the present day. The results of our study revealed about ten of more frequent uses and language strategies reported in a couple of exhaustive examples which even bring out the good aim of the social communication: to raise public awareness about moral and civil community issues.